A review of the classification of Dupuytren's disease. (February 2015) - Akhavani, M. A.; McMurtrie, A.; Webb, M.; Muir, L.
Although much has been published about the treatment of Dupuytren's disease, there is no clear consensus regarding the most effective form of treatment. Part of this uncertainty may result from the absence of a universal method of assessing this condition. We undertook a review of the literature in order to summarize the various methods by which Dupuytren's disease has been measured and quantified. We included all articles that offered a classification or assessment system for the disease. We excluded articles that dealt solely with surgical technique (although inevitably there was some overlap). We conclude that there are many methods of assessment, but that none of them is perfect and that further work is needed in the field.